KUALITAS SE’I SAPI YANG DITAMBAHKAN BUAH BELIMBING WULUH (Averrhoa bilimbi L) DENGAN LEVEL BERBEDA (Quality of se'i beef added bilimbi fruits (Averrhoa bilimbi l) with different levels) - Maria A. Epok; Gemini E.M. Malelak; Bastari Sabtu (Universitas Nusa Cendana, 2021)
The aims of this study was to evaluate the total bacterial colonies, antioxidant activity, lipid oxidation and organoleptic quality of se'i beef with the addition of bilimbi fruits (Averrhoa bilimbi L). The design used in this study was a completely randomized design (CRD) which consisted of 4 treatments and 3 replications. The treatments consisted of R0 = control (without the addition of Averrhoa bilimbi L), R1 = 2% addition of Averrhoa bilimbi L, R2 = 4% addition of Averrhoa bilimbi L and R3 = 6% addition of Averrhoa bilimbi L. The parameters observed included total bacterial colonies, antioxidant activity, lipid oxidation, aroma, color, taste and tenderness. The results showed that the administration of Averrhoa bilimbi L affected total bacterial colonies, antioxidant activity and lipid oxidation of se'i beef (P <0.01) where the higher the level of addition of Averrhoa bilimbi L, the higher the antioxidant activity value, the total number of bacterial colonies decreased The value of lipid oxidation decreased while the addition of Averrhoa bilimbi L 2%, 4%, 6% resulted in relatively the same aroma, color, taste and tenderness of se'i. It is concluded that processing se'i sapiwith the addition of Averrhoa bilimbi L at a level of 6% have a good effect on total bacterial colonies, antioxidant activity and lipid oxidation of se'i sapi.